2015
DOI: 10.1088/0264-9381/32/19/195014
|View full text |Cite
|
Sign up to set email alerts
|

Graviton loop corrections to vacuum polarization in de Sitter in a general covariant gauge

Abstract: We evaluate the one-graviton loop contribution to the vacuum polarization on de Sitter background in a 1-parameter family of exact, de Sitter invariant gauges. Our result is computed using dimensional regularization and fully renormalized with BPHZ counterterms, which must include a noninvariant owing to the time-ordered interactions. Because the graviton propagator engenders a physical breaking of de Sitter invariance two structure functions are needed to express the result. In addition to its relevance for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 149 publications
(497 reference statements)
1
65
0
Order By: Relevance
“…• For quantum gravity plus electrodynamics, inflationary gravitons induce secular effects on the dynamical photons and alter the electric field of a point charge and the magnetic field of a point magnetic dipole [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…• For quantum gravity plus electrodynamics, inflationary gravitons induce secular effects on the dynamical photons and alter the electric field of a point charge and the magnetic field of a point magnetic dipole [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The first line in this expansion comes from the first line of the full solution (10), and reproduces the massless solution (5) up to a constant. The second line above comes from the small mass expansion of the second line in (10). It is clear there is no singularity at the horizon even in this limit.…”
mentioning
confidence: 82%
“…Since the de Sitter invariant propagator has the issues described above, they use a non invariant propagator (which satisfies the same differential equation as the de Sitter propagator, but does not have the full de Sitter invariance). The analysis [41] however shows that an explicit non-invariant counterterm is required to cancel a loop divergence. Whether such a term is allowed in a consistent theory is unclear-explicit symmetry breaking in a gauge theory typically leads to violations of renormalizability and unitarity.…”
Section: Introductionmentioning
confidence: 98%
“…(3) Woodard and collaborators have suggested that the correct approach is to modify the graviton propagator ab initio (a few of these papers are [39][40][41]). Since the de Sitter invariant propagator has the issues described above, they use a non invariant propagator (which satisfies the same differential equation as the de Sitter propagator, but does not have the full de Sitter invariance).…”
Section: Introductionmentioning
confidence: 99%